THE URGENCY OF DEVELOPING MORAL AND SOCIAL VALUES FOR STUDENTS OF MADRASAH IBTIDAIYAH - Solahudin, Muhamad Nizan (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The stages of learners' moral and social development are important for educators to understand. Therefore, this article aims to examine the concept through a literature study method using an approach that emphasizes comprehensive analysis of relevant sources. The discussion focuses on Kohlberg's theory of moral development that highlights the stages of learners' morality, as well as Albert Bandura's social learning theory that emphasizes the role of imitation and modeling in the formation of behavior. The results show that some problems can disrupt learners' moral development at the conventional to post-conventional stages, and trigger deviant social behavior due to the influence of negative models from the surrounding environment. The implications for Madrasah Ibtidaiyah education require strengthening character education and more intensive social supervision, in order to instill moral values that are in accordance with religious and social norms.